Pengembangan Sistem Informasi Akuntansi untuk Meningkatkan Efisiensi dan Akurasi: Studi Kasus pada Implementasi Perubahan Program Akuntansi - Juvent Ade Pratama; Rayyan Firdaus (International Forum of Researchers and Lecturers, 2024)
This article discusses the development of accounting information systems to improve efficiency and accuracy, focusing on a case study of the implementation of accounting program changes. Previous studies have shown that effective accounting information systems can significantly improve the quality of accounting and managerial information. The implementation of accounting program changes often involves the integration of information technology to improve the process of financial reporting, internal control, and analysis of company performance. Previous studies have shown that companies that adopt information technology in their accounting systems have a competitive advantage in managing and analyzing financial information more efficiently. Important factors in the development of accounting information systems are the need to ensure data accuracy, reporting speed, and real-time availability of information for internal and external stakeholders. This study also explores the positive impact of the use of accounting information systems on the company's operational efficiency and strategic decision making. Successful implementations show that modern accounting information systems are able to integrate various business functions, such as finance, inventory, and manufacturing, to improve the coordination and effectiveness of the organization as a whole. Thus, the development of accounting information systems not only improves the company's internal processes but also enhances the company's adaptability to rapid and complex changes in the business environment. This study provides a strong theoretical foundation for understanding the importance of information technology integration in the context of accounting program changes to achieve higher efficiency and accuracy goals.